"Let the collective intelligence shine through": Crowdsourced Online Dispute Resolution from a Chinese Perspective. (3rd July 2018) - Gao, Wei
Abstract : An innovative type of dispute resolution model called crowdsourced online dispute resolution (CODR) has emerged in recent years and has the potential to offer an effective means for resolving disputes arising from online activities. Notable examples of this model are currently used in online opinion pools, online mock juries, and online dispute resolution by private companies. China's largest e-commerce platform Taobao.com has been testing this innovative approach since 2012. Its CODR system allows its users to sign up as panelists to resolve disputes between buyers and sellers. This paper analyzes how CODR systems can leverage "crowdsourced" approaches to deliver appropriate outcomes, drawing on extensive experience with Taobao's dispute resolution system, in particular its Public Jury. Given the enormity of Taobao's market share, such examination could prove instrumental in understanding the strengths and weaknesses of the model.